Factors influencing psychological well-being among firefighters in Sarawak and the role of coping behaviour as moderator - Mohamad Idres Rosdi (2024)
Psychological Well-Being (PWB) holds paramount importance in organizational settings, highlighting the pivotal role of each individual in nurturing a positive work environment and fostering effective teamwork. The research delves into the factors shaping PWB among Firefighters (FFs) at the Fire Rescue Department Malaysia (FRDM) in Sarawak, pinpointing Coping Behavior (CB) as a crucial variable predicting FFs’ coping mechanisms linked to PWB. Employing a descriptive approach, the study explores relationships among Malfunctioning Equipment (ME), Tedium/Boredom (TB), Co- worker Conflict (CC), Wages/Benefit Reduction (WB), PWB, and CB as a moderator. The primary objectives involve identifying the factors influencing FFs’ PWB in FRDM Sarawak, assessing CB’s role as a moderator, and evaluating relationships between independent variables (ME, TB, CC, WB) and the dependent variable (PWB), along with interpreting CB’s moderating effect. The respondents consist of FFs in FRDM Sarawak, with 142 out of 300 distributed online questionnaires collected. The study adopts a quantitative research method, utilizing SPSS version 24, SmartPLS version 3.2.8, and G*Power 3.1.9.7 for data analysis. Applying a multivariate logistic regression method, the study sets a factor analysis cut-off of 0.5 for item loading, and Average Variance Extracted (AVE) values ranging from 0.5 to 0.6 indicate construct acceptance. Most items exhibit factor loadings between 0.7 and 0.8, except for ME (0.452) and CB (0.460). Significant positive relationships are established between CC and WB toward PWB (β path coefficient = 0.072, t-value = 4.728, p-value = 0.000) and between WB and CB moderating PWB (β path coefficient = 0.059, t-value = 1.688, p-value = 0.046). Hypothesis findings suggest a significant relationship between CC and WB with CB as a moderator affecting FFs’ PWB. Only WB significantly correlates with the moderating effect on PWB. In summary, the study underscores the critical role of financial status as a determinant for PWB. Specifically, it establishes that Co-worker Conflict and Wages/Benefit Reduction are influential factors impacting the PWB of FFs in FRDM Sarawak. For future research, it is recommended to explore the financial commitments and their repercussions on workers in the service industry, as financial concerns, particularly related to WB reduction, may negatively influence performance.